Hematological analysis as a method of monitoring physiological status of medium carnivorous mammals in the Russian Far East - Galina S. Alekseeva; Mariya N. Erofeeva; Jose A. Hernandez-Blanco; Mikhail N. Litvinov; Mariya D. Chistopolova; Mariya D. Kim; Viatcheslav V. Rozhnov; Sergey V. Naidenko (Nature Conservation Research: Заповедная наука)
Clinical blood analysis is considered not only a method of assessing the health status of individuals, but also their fitness and welfare, although the interpretation of the obtained data is complicated by the combined influence of various factors. For most wild carnivore species, there is insufficient information about the effect of environmental factors on hematological parameters. Mammals in the Far East are exposed to hard seasonal climate changes, and therefore have physiological adaptations that enable them to survive the cold season. The aim of this study was to estimate the hematological parameters of three widespread species of medium carnivorous mammals in this region, namely Meles leucurus amurensis, Prionailurus bengalensis euptilura, and Nyctereutes procyonoides ussuriensis, taking into account such factors as sex, age and season in the Ussuriisky State Nature Reserve (Russia), as well as to identify the most informative blood indicators of the animal physiological status. In spring and autumn of 2014–2023, blood samples were collected from 103 individuals of the studied carnivores. The animals were captured, immobilised, blood-sampled and released in the wild at the capture site. The number of leucocytes was counted in the field, and their ratio was detected on the blood smears in the lab. The absence of sex differences and the presence of age differences in the studied species were revealed, which corresponds to the already known data on the parameters of mammalian blood. In spring, Nyctereutes procyonoides ussuriensis had higher leucocyte count (14.77 ± 1.76 mln/ml and 12.33 ± 1.08 mln/ml (hereinafter, in spring vs. autumn, respectively)), the ratio of neutrophils to lymphocytes (4.87 ± 0.47 and 3.02 ± 0.28), and the percentage of segmented neutrophils (73.12 ± 1.77% and 62.95 ± 2.29%), and the lower percentage of lymphocytes (20.35 ± 1.45% and 25.64 ± 1.49%) compared to autumn. Similar blood patterns were observed in two other species. This may be the result of a decrease in body mass and poor condition of animals, i.e. physiological stress after a long winter period and a lack of food resources. In addition, Nyctereutes procyonoides ussuriensis had higher percentages of eosinophils, basophils, and band neutrophils (7.85 ± 1.61%, 3.69 ± 1.26%, 2.15 ± 0.34%, respectively) than Meles leucurus amurensis (2.55 ± 1.09%, 0.45 ± 0.17%, 0.55 ± 0.18%, respectively) and Prionailurus bengalensis euptilura (1.48 ± 0.59%, 0.30 ± 0.16%, 1.74 ± 0.47%, respectively). These differences are probably determined by the biological characteristics of Nyctereutes procyonoides ussuriensis, since this species is an ideal host and carrier of various diseases, and it also has specific morphological features of blood cells. Thus, our results demonstrate the importance of systematic blood tests and the necessity of considering both species-specific characteristics and environmental factors for assessing animal health.